Impact of circular measures to reduce urban CO2 emissions: An analysis of four case studies through a production- and consumption-based emission accounting method. (20th December 2022) - Del Borghi, Adriana; Gallo, Michela; Silvestri, Nicolò; Baccelli, Oliviero; Croci, Edoardo; Molteni, Tania
Abstract: Cities are a major source of greenhouse gas emissions (GHGs), but they can play a significant role in climate change mitigation by adopting and implementing GHG emission reduction plans, policies and measures. Circular economy measures are recognized to contribute significantly to decarbonization. However, in the literature there is a lack of quantitative analyses on circular measures in cities and their impact on urban GHG emissions. The paper aims to contribute to the literature on the relation between circular cities and climate change mitigation by focusing on circular interventions applicable in three high-impact sectors in cities: energy systems, mobility and built environment, in order to investigate their impacts in terms of emission reductions and contribution to decarbonization. The study covers four cities around the world accounting for more than 10 million of inhabitants and 2, 000 km 2 of metropolitan area: Bogotá, Colombia; Genoa and Milan, Italy; Glasgow, UK. The methodology uses a Global Trade Analysis Project (GTAP) modelling approach to develop production and consumption-based emission baselines for the four cities and to assess impacts of selected circular measures in the three sectors on the baselines. According to the in-depth analysis of the four considered urban contexts, the majority of the emissions generated by activities carried out within the urban borders are emitted outside the borders in the form of emissions scope 3, thus demonstrating how today's cities are large consumers of goods produced outside their borders, requiring the use of a consumption-based approach for emissions inventory. The results on the modelling of the GHG reduction impact of circular measures show that there is a relevant emission reduction potential in Scope 1 and 2 emissions in cities and highlight the need to prioritize decarbonization of electricity supply in order to ensure relevant emission reductions across the three sectors. The results also demonstrate the potential to reduce supply-chain Scope 3 emissions through urban measures. Graphical abstract: Image 1 Highlights: Four different urban contexts around the world are taken in account. Three sectors are investigated: energy, mobility and built environment. A consumption-based emission accounting method is used to assess the effective impact of cities. Impacts of different GHG emission reduction interventions are evaluated for each city.